PREVALENCE OF COMORBIDITIES AMONG DIABETIC PATIENTS OF JINJA REGIONAL REFERRAL HOSPITAL. A CROSS-SECTIONAL STUDY. - ALIMWENDA, VIOLET; Kajubi , Richard; Atuhaire , Hilary; Anahita , Ali (Student's Journal of Health Research Africa, 2024)
Background Diabetes is a complex and multifaceted condition that is often accompanied by comorbidities, which are additional health conditions that co-occur with diabetes. Study aims to assess the Prevalence of comorbidities among diabetic patients of Jinja regional referral hospital. Methodology A descriptive cross-sectional study that employed quantitative data techniques was used. Simple random sampling was used to select participants in the study. Descriptive statistics was used to assess the frequency distribution of the three risk categories. A Chi-square test assessed the categorical variables and trends in the prevalence of diabetic comorbidities. Results 185(65.1%) of the respondents were females while 99(34.9%) were males. The number of patients with high cholesterol levels was 94(33.1%). The number of patients who were HIV positive was 67(23.6%). Patients who had eye problems were 64(22.5%). Patients with kidney problems were 51(18%) and heart or brain problems were 78(27.5%). Patients with footing problems were 36(12.7%). The number of patients with DPN was 75(26.4%). Patients with comorbidities were 104(36.6%) and the number of patients without comorbidities was 180(63.4%). The prevalence of diabetic comorbidities was 36.6%. The number of patients with eye problems (retinopathy) was 64, kidney problems were 51, heart problems was 78, footing problems (diabetic foot) was 36, and peripheral neuropathy was 75. Conclusion The prevalence of comorbidities was high given the scarcity of resources and delayed diagnostic management of diabetic complications. Recommendations The Ministry of Health should put more strategies to improve early diagnosis and management of Diabetes and its comorbidities.